Thinking Big: Lessons Learned from a Landscape-Scale Approach to Coastal Habitat Conservation. Issue 3 (3rd May 2016) - Chabot, Helen; Farrow, Dan; York, Dawn; Harris, Janine; Cosentino-Manning, Natalie; Watson, Lani; Hum, Kim; Wiggins, Chad
ABSTRACT: While historically many coastal habitat conservation activities have focused on single projects and "low-hanging fruit, " there is increasing interest in strategically addressing habitat challenges at landscape scales. Zooming out to identify large-scale conservation needs and areas of greatest impact can yield significant ecological and economic benefits, but requires a new way of thinking and working that can be challenging. Based on a session convened at the Restore America's Estuaries/The Coastal Society Summit in November 2014, this article explores the concept of landscape-scale conservation, describes how it aligns with the National Oceanic and Atmospheric Administration Habitat Blueprint initiative, and provides case studies of ongoing landscape-scale efforts in three coastal areas: the Cape Fear River in North Carolina; the Russian River Watershed Habitat Focus Area in California; and the West Hawai'i Habitat Focus Area. These examples illustrate both the benefits and the challenges of taking a landscape-scale approach to habitat conservation. While a landscape-scale approach provides a strong framework for planning, in practice success also depends heavily on building strong partnerships, engaging stakeholders, and maintaining flexibility to adapt to changing conditions and take advantage of opportunities as they arise.